Visualizing physical, electronic, and optical properties of organic photovoltaic cells - Pfannmöller, Martin; Kowalsky, Wolfgang; Schröder, Rasmus R. (Energy & environmental science, 2013)
The most interesting active layer system for organic photovoltaic cells is the bulk heterojunction (BHJ). The general structure of a BHJ is a network of domains, which contain blended donor and acceptor molecules, often in pure and mixed phases. Directly visualizing this nanoscale phase separation of BHJs and corresponding morphological parameters has attracted much interest and has led to novel insights into their physical properties. Imaging methods that have been proven to be of great importance are scanning probe, scanning X-ray, and electron microscopy. Early works successfully employed conventional contrast mechanisms at high resolution for correlation of structure and function. Many imaging techniques also offer analytical capabilities using specific interactions of the probes with different material domains. Resulting material contrasts can be converted into morphological maps by correlation with the intrinsically different physical, electronic, and optical sample properties. Spatially resolved visualization of these properties is crucial to provide answers to questions about fundamental processes that determine the solar cell performance. A major paradigm shift was initiated by the discovery that instead of a completely separated network of donor and acceptor domains, a multiphase system is beneficial for enhanced photo-physical properties. Thereby phases differ in ordering, orientation and composition. In this review, we provide an overview of techniques and recent approaches for imaging BHJ structures at the nanoscale. Advantages and disadvantages of the underlying contrast mechanisms are summarized. In addition, we introduce best practices for the application of transmission electron microscopy (TEM) by comparing enhanced conventional and analytical modes.